2013
DOI: 10.1177/0954410013478255
|View full text |Cite
|
Sign up to set email alerts
|

Detonation-driven–shock wave interactions with perforated plates

Abstract: The study of detonations and their interactions is vital for the understanding of the high-speed flow physics involved and the ultimate goal of controlling their detrimental effects. However, producing safe and repeatable detonations within the laboratory can be quite challenging, leading to the use of computational studies which ultimately require experimental data for their validation. The objective of this study is to examine the induced flow field from the interaction of a shock front and accompanying prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It has been shown that grids or perforated plates modify the flow field by introducing new shock waves, regions of vortices, and considerable turbulence in which the energy of the incident shock wave can be dissipated. Thereafter, several studies discussing the attenuation of a shock wave passing through a perforated plate were achieved with a shock tube [8][9][10][11]. In [12], a transonic shock tube was used to visualize the interaction of a blast wave profile with a metallic perforated plate and three types of grid with different porosities were tested.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that grids or perforated plates modify the flow field by introducing new shock waves, regions of vortices, and considerable turbulence in which the energy of the incident shock wave can be dissipated. Thereafter, several studies discussing the attenuation of a shock wave passing through a perforated plate were achieved with a shock tube [8][9][10][11]. In [12], a transonic shock tube was used to visualize the interaction of a blast wave profile with a metallic perforated plate and three types of grid with different porosities were tested.…”
Section: Introductionmentioning
confidence: 99%